ICT-supported for participatory engagement within E-learning community - Noor Hida Natrah Aziz; Haryani Haron; Afdallyna Fathiyah Harun (Institute of Advanced Engineering and Science, 2020)
This paper presents ICT-supported for participatory engagement learning within the e-learning community. Effectively tools in e-Learning facilitate interactive learning and the achievement of desired learning outcomes for learners. However, the intensity of its usage is not very remarkable; there is a need to understand ICT- supported for learners from the perspectives of participatory engagement. Therefore, integrating suitable technology into e-learning is expected to strengthen learner's engagement within the e-learning community. The objective of the study is to identify technology that could effectively support learners' engagement. This study analyzes the available technology in the market to integrate into e-learning using the technology evaluation process. Interview sessions with experts were held to validated and suggested other technology uses in e-learning. This research is carrying out with three experts (academic staff) of the e-technologies within the University. This study uses semi-structured interviews to captured expert suggestions, knowledge, and expertise about technologies. Understanding learner's requirements toward technology are essential to ensure learners can reap the benefits of technology usage. This study uses a thematical analysis to identify and organize key themes from qualitative data. The result reveals mobile technology, wireless technology, live streaming technology, authoring tool, summative assessment, cloud computing, gamification and Instagram is suitable technologies that support participatory engagement activities.